2007
DOI: 10.1016/j.brainres.2006.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Corpus callosum morphology and ventricular size in chromosome 22q11.2 deletion syndrome

Abstract: In this paper, novel methods were used to map the corpus callosum morphology of children with chromosome 22q11.2 deletion syndrome in order to further investigate changes to that structure and to examine their possible effects on cognitive function. The callosal profiles were extracted from the centermost MRI midsagittal slice by supervised thresholding and the structure's boundary and midline were computed automatically. Difference analysis was based on non-rigid registration, in which a template image is war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 49 publications
2
50
0
1
Order By: Relevance
“…Having demonstrated (Simon et al 2005a) that children with DS22q11.2 could not perform as well as TD controls children, we used a new task requiring children to simply choose the larger of a pair of objects, either bars varying in length differences of 1 to 7cm or Arabic numbers varying in numerical differences of 1 to 7. . Our results (Simon et al 2007) show both a significant increase in response time for all distances and significantly greater response times with increasing number in the DS22q11.2 group. Slopes for distances 1−5 indicated were significantly larger for the DS22q11.2 than the TD group (p=.001); DS22q11.2 97.86ms/distance vs. TD 45.43ms/distance for blocks and 100.29ms/distance vs. 30.88ms/distance for numbers.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Having demonstrated (Simon et al 2005a) that children with DS22q11.2 could not perform as well as TD controls children, we used a new task requiring children to simply choose the larger of a pair of objects, either bars varying in length differences of 1 to 7cm or Arabic numbers varying in numerical differences of 1 to 7. . Our results (Simon et al 2007) show both a significant increase in response time for all distances and significantly greater response times with increasing number in the DS22q11.2 group. Slopes for distances 1−5 indicated were significantly larger for the DS22q11.2 than the TD group (p=.001); DS22q11.2 97.86ms/distance vs. TD 45.43ms/distance for blocks and 100.29ms/distance vs. 30.88ms/distance for numbers.…”
supporting
confidence: 52%
“…We recently reported (Machado et al 2007) that at least one change in the corpus callosum (its area) relates quite differently to performance on the attentionally demanding counting part of the enumeration task described earlier in children with DS22q11.2 than in TD controls. This suggests that affected children may be using a different, and atypical, cortical network to complete this task and this may partially explain their difficulties.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies in children with 22q11DS had examined the area of the CC in the mid-sagittal plane, [20][21][22] but differences in fiber density within the CC can result in asymmetries that, in turn, can affect area measurements. 34 Volumetric measurements are less subject to such variances and would thus be more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…19 We previously reported that the CC area was larger in children with 22q11DS, compared with typically developing children, 20 replicated by others. [21][22][23] Relatively little is known about the association between the CC size and the neurocognitive/psychiatric manifestations of 22q11DS, with one report of an association between ADHD and smaller CC area 21 and another of faster enumeration skills with a larger CC. 22 Our main objective in this study was to examine volumetric differences in the CC in children with 22q11DS in relationship to neuropsychological manifestations and specific functional singlenucleotide polymorphisms (SNPs) within the COMT (rs4680 or Val 158 Met ), ZDHHC8 (rs175174), PRODH (rs450046) and UFD1L (rs5992403) genes, within the corresponding 1.5-Mb interval of the 22q11.2 region.…”
Section: Introductionmentioning
confidence: 99%